2018
DOI: 10.1111/cdev.13069
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Forgiveness in Young Children

Abstract: Humans depend greatly on our cooperative relationships. Thus, when our relationships are damaged by transgressions, they need to be repaired. Such repair requires that the transgressor show remorse and the victim forgive. Previous research demonstrates that as transgressors, young children show remorse and attempt to repair the harm they caused. However, it remains unclear when children, as victims, forgive remorseful transgressors. In Study 1, 5-, but not 4-year-olds, (n = 20 each) were more forgiving of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 36 publications
1
52
0
3
Order By: Relevance
“…By contrast, recent evidence suggests that forgiveness in childhood may already function as a meaningful mechanism for repairing or maintaining relationships (Oostenbroek & Vaish, ; Van der Wal, Karremans, & Cillessen, ). Research also shows that children's self‐reported likelihood of forgiving is a function of interpersonal and psychological features of the situation, such as the offender's apology and intention.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…By contrast, recent evidence suggests that forgiveness in childhood may already function as a meaningful mechanism for repairing or maintaining relationships (Oostenbroek & Vaish, ; Van der Wal, Karremans, & Cillessen, ). Research also shows that children's self‐reported likelihood of forgiving is a function of interpersonal and psychological features of the situation, such as the offender's apology and intention.…”
Section: Introductionmentioning
confidence: 97%
“…However, with few exceptions (e.g., Oostenbroek & Vaish, ), extant research was conducted using hypothetical stimuli. Notably, however, judgments about hypothetical events are made from a detached stance whereas actual forgiveness is granted by someone feeling hurt or angry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forgiveness is defined as overcoming negative feelings associated with the perception of being hurt by another individual [Lippman et al, ]. Forgiveness of transgressors has been shown to develop in 4‐ and 5‐year‐old children [Oostenbroek & Vaish, ]. Forgiveness is associated with global mental health, life satisfaction, positive affect, and self‐esteem [Van Dyke & Elias, ].…”
Section: Introductionmentioning
confidence: 99%